The Determinants and Effects of Social Connectedness in Europe - Michael Bailey; Theresa Kuchler; Dominic Russel; Bogdan State; Johannes Stroebel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We use aggregated data from Facebook to study the structure of social networks across European regions. Social connectedness declines strongly in geographic distance and at country borders. Historical borders and unions — such as the Austro-Hungarian Empire, Czechoslovakia, and East/West Germany — shape present-day social connectedness over and above today's political boundaries. All else equal, social connectedness is stronger between regions with residents of similar ages and education levels, as well as between those that share a language and religion. In contrast, region-pairs with dissimilar incomes tend to be more connected, likely due to increased migration from poorer to richer regions. We find more socially connected region-pairs to have more passenger train trips between them, even after controlling for distance and travel time. We also find that regions with a higher share of connections to other countries have higher rates of trust in the E.U. and lower rates of voting for anti-E.U. political parties.
Keywords: D72; J61; O52; R23; Z13; 330; social connectedness; Europe; homophily; border effects; migration